Information Needs of Sericulture Research Workers: A Study with Respect to Information Needs of Sericulture Scientists in India - Manjunatha, K. K.; Asundi, A. Y. (Journal of Information and Knowledge, 2014)
A study of the information requirements of sericulture research workers is made. The needs for information of sericulture scientists in India are studies considering various parameters the types, preferences and difficulties of the sericulture scientists are studies.